In harm's way Traumatic brain injury in young children - New Mexico Aging and Long Term Services Department (Santa Fe, NM State of New Mexico, U.S. Department of Health and Human Services., 2010)
This discuses brain injuries with young children, ages 0-4. Topics included are Definition, Causes, Incidednce in young children; Importance of early identification and effects of delayed diagnosis; Failures in identification; Shaken Baby Syndrome and normal infant crying; Common signs and symptoms of TBI in children; Addressing undiagnosed but suspected TBI; Addressing know TBIs; and Prevention.
Brain injury awareness for Head Start providers.
Keywords: Traumatic brain injury - Infants. -- Tramatic brain injury - Children